Women's Knowledge Toward the Side Effects of Hormonal Birth Control Pills - Asmaa Hammooz (Universitas Muhammadiyah Sidoarjo, 2025)
Objectives: The study's goals were to assess women's awareness of the negative effects of hormonal contraceptives and determine how that awareness related to their demographic traits. Methods: At hospitals in the Al-Qadisiyah Governorate, a descriptive cross-sectional study was carried out to find out how much women knew about the negative effects of hormonal contraceptives. It was decided to prolong the study term from April 3, 2025, to July 25, 2025. Data collection was rescheduled from May 3, 2025, to June 2, 2025—purposive non-probability sample. (300) was the sample that was used. To participate in the study, participants fill out a form that is split into two sections: a demographic data form and information about the negative effects of hormonal contraceptive pills (11). Results: The results of this investigation showed that the most common general evaluation of knowledge among students was poor, and the mean (1.96) Conclusion: The overall assessment was a low level of knowledge, with a percentage of 39.6%. Highlights: Low awareness of contraceptive side effects among women. Education level significantly influences knowledge. Targeted interventions can improve reproductive health. Keywords: Women, Contraceptives, Knowledge, Side Effects, Education